2014
DOI: 10.1167/iovs.13-13831
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Human Corneal Epithelial Thickness Measured With Anterior Segment Optical Coherence Tomography

Abstract: The paracentral corneal epithelium, as well as the nasal and temporal limbal epithelium, became thinner with aging, while the central CET seemed to remain constant. Measurement with AS-OCT of the corneal and limbal ET could aid in clinical assessment and planning treatments of the cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
88
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 49 publications
15
88
2
Order By: Relevance
“…Kanellopolous and Asimellis noted that the topographic variability of CET increased with age in their study population, but they did not find age-related differences in CET [2]. To the contrary, Yang and associates reported age-related thinning of the corneal epithelium, especially in the peripheral and limbal regions [16], which is in agreement with the results of our study. One possible reason for these inconsistencies is the presence of uncontrolled confounding factors affecting corneal thickness or ET measurement.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Kanellopolous and Asimellis noted that the topographic variability of CET increased with age in their study population, but they did not find age-related differences in CET [2]. To the contrary, Yang and associates reported age-related thinning of the corneal epithelium, especially in the peripheral and limbal regions [16], which is in agreement with the results of our study. One possible reason for these inconsistencies is the presence of uncontrolled confounding factors affecting corneal thickness or ET measurement.…”
Section: Discussionsupporting
confidence: 91%
“…In the corneal epithelium, age-related changes consisting of decreases in basal epithelial cell density at the limbus have been noted, but in the same studies the morphology and density of both the superficial and the basal cells showed no changes [13,14]. Some authors using very high frequency (VHF) digital ultrasound and spectral domain-OCT reported no correlation between CET and age [1,15], but a recent, large-scale population study found thinning of the CET in the midperiphery with age [16]. One possible explanation for the inconsistencies in the results of these studies is uncontrolled confounding factors affecting the corneal thickness or ET measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another study found the epithelial thickness to thin only in the nasal and limbal zones. 20 Our study found no correlation of age with epithelial thickness in almost all zones and therefore we agree with Wang et al 17 and Reinstein et al This large discrepancy can be explained by the positive correlation of epithelial thickness variability with age; Kanellopoulos et al 4 described this relationship. They recorded the thickness of the epithelium on four different occasions in 373 individuals and observed the difference in each recording.…”
Section: Agesupporting
confidence: 81%
“…Age-related thinning of corneal epithelium has been observed using the FD-OCT, especially in the peripheral and limbal regions. 11 Wang et al 17 reported that the cornea is thicker in high myopia, but that the CET does not differ; however, the same investigators did not control for the differences in gender ratio between the normal and high myopia groups, despite recognizing that gender may affect the corneal thickness. Importantly, most previous researchers have not controlled for potential confounding factors when investigating the correlations between their specific factors of interest and the CCT or CET.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 Several methods have been used to measure CET: optical pachymetry, 6 confocal microscopy through focusing, 7,8 very-high-frequency ultrasound, 4,9 and optical coherence tomography (OCT). 3,[10][11][12] Specifically, Fourier-domain OCT (FD-OCT) is a powerful, noninvasive technique that can provide cross-sectional images of the anterior and posterior surfaces of the cornea with a high scanning speed and resolution. Recent studies have reported good repeatability of the corneal thickness and CET measurements, using the RTVue system (Optovue Inc, Fremont, CA), in both normal and post-laser in situ keratomileusis (LASIK) eyes.…”
mentioning
confidence: 99%